2021
DOI: 10.1186/s12903-021-01826-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of magnetic resonance imaging in distinguishing temporomandibular disorders: a retrospective chart review

Abstract: Background This study was to evaluate the diagnostic significance of Magnetic Resonance Imaging (MRI) in distinguishing temporomandibular disorders (TMD). Methods A total of 684 patients with TMD were included in the study. Diagnosis for TMD was conducted according to the international criteria. Two professional radiologists were selected for professional training, and the Kappa values were compared for the diagnosis results to determine the consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…More importantly, MRI demonstrates the degenerative changes years before they clinically manifest [ 49 ]. Finally, osteoarthritic changes are followed by transient pain, present only in the active phase of the disease [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, MRI demonstrates the degenerative changes years before they clinically manifest [ 49 ]. Finally, osteoarthritic changes are followed by transient pain, present only in the active phase of the disease [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Temporomandibular joint disorder (TMJD) represents a major category of TMD; although, occasionally, it is not associated with painful symptoms [19]. Radiological studies, especially magnetic resonance imaging (MRI) have confirmed the various clinical signs elicited in patients with TMJD [20]. Pathophysiologically, a dysfunctional, abnormal TMJ cannot be considered as an isolated disorder.…”
Section: Introductionmentioning
confidence: 99%